Facing or retreating? Evaluating the impact of fiscal pressure and the selection preference of tax efforts among Chinese local government - Deyun, Zhen; Yiqing, Pan (Frontiers in Environmental Science, 2023)
As China's economy enters a new era, fiscal pressure is growing rapidly. How will local governments determine their tax efforts under pressure? Facing or retreating? This paper selects macro data of 30 provincial administrative regions from 2000 to 2018, using instrumental variable method and threshold regression model, while, putting fiscal pressure, land-transferring fees, local government debt and transfer payments into the same regression equation to test the causal relationship between fiscal pressure and local tax efforts. We found that local governments will choose to raise tax efforts under fiscal pressure. Moreover, the heterogeneity analyses prove that eastern local governments prefer higher tax efforts. When the growth rate of tax and economy is low, local governments have less motivation to strengthen tax collection and administration. Threshold regression tests show that transfer payments have a moderating effect on local tax efforts, and transfer payments has a threshold effect. When the transfer payments are under the minimum threshold value or above the maximum threshold value, it may lead to inaction of local governments, who do not try their best to raise tax efforts. These findings are valuable in policy making for the construction of sustainable public finance.